Catalytic Plasticity of Germacrene A Oxidase Underlies Sesquiterpene Lactone Diversification. Issue 3 (18th September 2019) - Nguyen, Trinh-Don; Kwon, Moonhyuk; Kim, Soo-Un; Fischer, Conrad; Ro, Dae-Kyun
Abstract : The striking catalytic plasticity of germacrene A oxidase, an evolutionary conserved enzyme in the Asteraceae, has led to the existence of diverse sesquiterpene lactones, including artemisinin. Abstract: Adaptive evolution of enzymes benefits from catalytic promiscuity. Sesquiterpene lactones (STLs) have diverged extensively in the Asteraceae, and studies of the enzymes for two representative STLs, costunolide and artemisinin, could provide an insight into the adaptive evolution of enzymes. Costunolide appeared early in Asteraceae evolution and is widespread, whereas artemisinin is a unique STL appearing in a single Asteraceae species, Artemisia annua . Therefore, costunolide is a ubiquitous STL, while artemisinin is a specialized one. In costunolide biosynthesis, germacrene A oxidase (GAO) synthesizes germacrene A acid from germacrene A. Similarly, in artemisinin biosynthesis, amorphadiene oxidase (AMO) synthesizes artemisinic acid from amorphadiene. GAO promiscuity is suggested to drive the diversification of STLs. To examine the degree of GAO promiscuity, we expressed six sesquiterpene synthases from cotton ( Gossypium arboretum ), goldenrod ( Solidago canadensis ), valerian ( Valeriana officinalis ), agarwood ( Aquilaria crassna ), tobacco ( Nicotiana tabacum ), and orange ( Citrus sinensis ) in yeast to produce seven distinct sesquiterpene substrates (germacrene D, 5- epi -aristolochene, valencene, δ-cadinene, α- and δ-guaienes, and valerenadiene). GAO or AMO was coexpressed in these yeasts to evaluate the promiscuities of GAO and AMO. Remarkably, all sesquiterpenes tested were oxidized to sesquiterpene acids by GAO, but negligible activities were found from AMO. Hence, GAO apparently has catalytic potential to evolve into different enzymes for synthesizing distinct STLs, while the recently specialized AMO demonstrates rigid substrate specificity. Mutant GAOs implanted with active site residues of AMO showed substantially reduced stability, but their per enzyme activities to produce artemisinic acid increased by 9-fold. Collectively, these results suggest promiscuous GAOs can be developed as novel catalysts for synthesizing unique sesquiterpene derivatives.